2005
DOI: 10.1590/s0021-75572005000300011
|View full text |Cite
|
Sign up to set email alerts
|

Colonização nasofaríngea pelo Streptococcus pneumoniae em crianças com doença falciforme usando penicilina profilática

Abstract: Objectives: To determine the prevalence of nasopharyngeal pneumococcus colonization in children with sickle cell disease undergoing penicillin prophylaxis, to identify risk factors for colonization and to serotype and determine antibiotic resistance in pneumococci obtained from those children. Between April 9, 2002 and February 28, 2003, 188 nasopharyngeal swabs were obtained from 98 children with sickle cell disease in follow-up at the Hospital São Paulo Universidade Federal de São Paulo. Pneumococci were is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
2
1
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 25 publications
4
2
1
1
Order By: Relevance
“…Patients with HbSC and HbSβ + should demonstrate better preserved splenic function in the first five years of life than patients with HbSS and HbSβ, determining a better immune response, and therefore, lower risk of invasive pneumococcal disease [24]. Verifying if colonization rate could also be different according to genotypes, we found no difference in the multivariate analysis, which was also observed in previous studies [6,17].…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Patients with HbSC and HbSβ + should demonstrate better preserved splenic function in the first five years of life than patients with HbSS and HbSβ, determining a better immune response, and therefore, lower risk of invasive pneumococcal disease [24]. Verifying if colonization rate could also be different according to genotypes, we found no difference in the multivariate analysis, which was also observed in previous studies [6,17].…”
Section: Discussionsupporting
confidence: 85%
“…Other authors found colonization rates among children with SCD taking penicillin ranging from 8% to 15.5% [11,17,18]. In the Brazilian study published in 2005, we found similar results, with a colonization rate of 13.3% [6]. In none of these studies, patients received the PCV 7.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Entre os defeitos imunológicos descritos estão: diminuição da produção de interleucina 4, com comprometimento da maturação do linfócito B e da produção de IgM; contagem variável de linfócitos T helper e supressor; redução nos níveis de linfócitos T helper e supressor nos pacientes com asplenia funcional; rápida multiplicação bacteriana no sangue devido aos altos níveis de ferro e transferrina circulantes; produção de Acs inadequada frente a administração EV de vacinas polissacarídica. 25,27,28 A alteração da função esplênica nesses pacientes determina além da perda da capacidade de filtração mecânica, a diminuição da opsonização por menor síntese de opsoninas e pela alteração funcional da via alternativa e clássica do complemento, resultando em fagocitose e morte intracelular ineficazes, principalmente para as bactérias encapsuladas 29 O risco da criança falciforme adquirir infecção pelo pneumococo quando comparado com a população normal é trinta a cem vezes maior para bacteremia e quatrocentas vezes maior para sepse ou meningite; já em relação ao hemófilus o risco é cerca de duas a quatro vezes maior. 28,30,31 Esses pacientes também são mais susceptíveis a infecções por Salmonella sp e germes gram negativos.…”
Section: Infecções No Paciente Falcêmicounclassified